Flood Modeling of the Batang Sungai Lengayang Area with Hec-Ras Program - Zaidina Resvita islami; Yaumal Arbi (CIVED, 2025)
Floods are disasters that disrupt human life caused by human and natural factors. Natural conditions that affect flooding in West Sumatra are rainfall patterns in water areas, sea surface temperature patterns, and whirlpool patterns in the Indian Ocean. Batang Lengayang is a river that is prone to flooding. Floods in the Batang Lengayang river occur every year, especially during the rainy season. According to the Central Statistics Agency of Pesisir Selatan Regency, in Lengayang District, floods were recorded 5 times throughout 2020, 8 times in 2021, and 10 times in 2022. Meanwhile, in 2024, there was also a flash flood on March 7 which was caused by very high rainfall intensity and on a long time scale. This study aims to determine the flood discharge of the Batang Lengayang river with a return period of 50 and 100 years. Furthermore, this study also aims to model the Batang Lengayang river flood using HEC RAS. And to determine the area of ​​flood inundation of the Batang Lengayang river for a return period of 50 and 100 years. The results of the study showed that the 50-year return period produced a maximum flood discharge of 399 m³/second and the 100-year return period produced a maximum flood discharge of 444.46 m³/second. The modeling results showed that the flood area increased with the addition of the return period. The flood area obtained was 376 ha or 3.7 km² for the 50-year return period and 412 ha or 4.12 km² for the 100-year return period.